PENGARUH FINANCIAL TECHNOLOGY PAYMENT, LITERASI KEUANGAN, RELIGIUSITAS DAN FRUGAL LIVING TERHADAP PERILAKU KEUANGAN MAHASISWA DI ERA DIGITAL - Sulastiningsih Sulastiningsih; Wahyu Purwanto; Muhammad Awal Satrio Nugroho; Yunita Fitri Wahyuningtyas (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2026)
The purpose of this research is to analyze the influence of fintech payment, financial literacy, religiosity and frugal living both partially and simultaneously on the financial behavior of STIE Widya Wiwaha students. This research is quantitative research, sample determination using proportional sampling, type of primary data collected with a likert scale questionnaire as a research instrument. Before conducting the hypothesis testing a validity and reliability test was conducted to test the quality of the data and to test the classical assumption of regression, namely multicollinearity, heteroskedasticity and normality. The research results concluded that financial literacy and frugal living have a significant positive influence on financial behavior, but fintech payment and religiosity do not affect financial behavior. Simultaneously the four variables have an influence on financial behavior, the contribution of the influence of the independent variable on the dependent variable is 59,6%. The implication of this research result is to provide practical inspiration for students and the public to improve financial literacy and maintain a frugal lifestyle so that financial behavior becomes better and healthier. Besides, the public needs to interpret more wisely about the use of fintech and religiosity towards the religion they believe in so that it can have a positive impact on financial behavior.